Self-confidence in mathematics: a case study on engineering technology students in FTK, UTeM - Waini, Iskandar; Hamzah, Khairum; Mohd Said, Rahaini; Miswan, Nor Hamizah; Zainal, Nurul Amira; Ahmad, Aminah (International Educative Research Foundation and Publisher, 2014)
Self-confidence towards the studied subject is very important in order for students to succeed in their field of study. There is some relationship between self-confidence and the students’ achievement. The main objective of this study was to understand and examine Engineering Technology (ET) students’ attitudes towards the level of self-confidence or self-efficacy in mathematics during their class sessions at the Faculty of Engineering Technology (FTK), Universiti Teknikal Malaysia Melaka (UTeM). This study investigated the attitudes of 332 second year students in several field of studies at FTK, UTeM in the second semester of the 2013/2014 session. Students were given a set of questionnaire consisting of statements on their attitudes towards self-confidence in mathematics. This activity was performed during one of the classes. From the findings, a conclusion was drawn regarding the attitudes of ET students towards self-confidence in mathematics. The result shows that most ET students had positive self-confidence in mathematics. However, the level of confidence was not as high and depended on the students’ situations and current environment.